Automated Depth Selection for the Fairsheet - Brouwer, G. K. (The International Hydrographic Review, 2015)
In order to cover as much as possible of North Sea bottom depth characteristics a lot more data is sampled than the depth figures actually appearing on the fairsheet. During the past three years the Netherlands Hydrographic Service has developed a program for automated depth selection as part of the HYDRAUT system ashore [1], This program was initiated by P. van der Molen and A.B. Wilbrink [2], but several modifications have had to be made to match problems encountered in its first operational phase (Spring 1975). Depth selection from a hydrographic viewpoint should meet two criteria : minimum depths have highest priority, whereas a true representation of the sea-bottom relief should appear on the fairsheet.